1982
DOI: 10.1207/s15327752jpa4601_13
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptualization and Measure of Argumentativeness

Abstract: A conceptualization and measure of argumentativeness is reported. Argumentativeness was conceptualized as a trait Which is composed of the tendency to approach arguments and the tendency to avoid arguments. A 20-item, self-report scale was developed in a series of three factor analytic studies. The internal consistency and test-retest reliabilities of the scale were high. A series of additional studies yielded considerable evidence as to the validity of the scale. The conceptualization of argumentativeness acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
379
0
38

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(427 citation statements)
references
References 10 publications
10
379
0
38
Order By: Relevance
“…In the present study, characteristics emerging from teachers who avoid arguments are withdrawing from expressing arguments with students, insisting on their point of view thinking that it's the right thing to do and imposing their opinion through punishments, threats or yelling. This finding is in consistency with the findings of Infante and Rancer (1982) suggested that low scores of argumentativeness are expected to depict individuals who avoid disputing, are quite compliant and easily manipulated in a way which violates even their most important interests. As a consequence, verbal aggressiveness is enhanced and plays the role of discipline, while at the same time PE teachers support that effective teaching is the outcome of a disciplinary class (Bekiari & Hasanagas, Psychology 2016c;Jones, 2014;Lefstein, 2002;Matsagouras, 2008;Mohapi, 2014;Nelson, 2002;Parker, 1995;Placek & Dodds, 1988;Sharkey & Fenning, 2012;Wang, Selman, Dishion, & Stormshak, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, characteristics emerging from teachers who avoid arguments are withdrawing from expressing arguments with students, insisting on their point of view thinking that it's the right thing to do and imposing their opinion through punishments, threats or yelling. This finding is in consistency with the findings of Infante and Rancer (1982) suggested that low scores of argumentativeness are expected to depict individuals who avoid disputing, are quite compliant and easily manipulated in a way which violates even their most important interests. As a consequence, verbal aggressiveness is enhanced and plays the role of discipline, while at the same time PE teachers support that effective teaching is the outcome of a disciplinary class (Bekiari & Hasanagas, Psychology 2016c;Jones, 2014;Lefstein, 2002;Matsagouras, 2008;Mohapi, 2014;Nelson, 2002;Parker, 1995;Placek & Dodds, 1988;Sharkey & Fenning, 2012;Wang, Selman, Dishion, & Stormshak, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Five communicational PE teachers' profiles have been detected according to the approach and avoidance of arguments during the lesson, as well as the usage of verbal aggressiveness via the frequency and intensity of verbally aggressive messages. More precisely these are, "high argumentativeness-low verbal aggressiveness" "moderate argumentativeness and verbal aggressiveness", "moderate argumentativeness-low verbal aggressiveness", "low argumentativeness-high verbal aggressiveness", "low argumentativeness-moderate verbal aggressiveness", as presented in previous research (Infante & Rancer, 1982, 1996. According to the emerging profiles when PE teachers approach arguments and are capable of arguing, they are less likely to expose a verbally aggressive behavior (Bekiari, 2016;Infante & Rancer, 1996;Infante et al, 1984;.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…There have been studies with a focus on argumentative traits. Prunty et al found that the U.S. students were higher in trait argumentativeness (Infante & Rancer, 1982) than Japanese students, which is consistent with the finding by Suzuki (1990). However, when M. S. Kim et al (2001) compared three cultural groups-Korea, Hawaii, and the mainland U.S.-as a part of their model testing study, they found no significant differences in the overall argumentativeness scores.…”
Section: Introductionsupporting
confidence: 71%
“…quoted in Nakamura, 1964, p. 539) 14 . Moreover, studies that have compared the argumentativeness of different populations (using the scale developed by Infante & Rancer, 1982) have found only minor and inconsistent differences between Easterners and Westerners (Aune, Hunter, Kim, & Kim, 2001;Bresnahan, Shearman, Lee, Ohashi, & Mosher, 2002). Finally, experiments on collaborative reasoning show that Chinese and Korean children can shed very quickly the constraints that may be imposed during interactions with teachers to become fierce arguers between themselves (Dong, Anderson, Kim, & Li, 2008).…”
Section: Socio--cultural Argumentsmentioning
confidence: 99%